Existe associação entre a fraqueza dos músculos do quadril e a dor lombar crônica não específica? estudo transversal do tipo caso-controle - Pizol, Gustavo Zanotti (2021)
Introduction: Changes in the motor control of the lumbopelvic region have been reported in patients with chronic non-specific low back pain. In these patients, the function of the hip muscles is assessed using both quantitative and clinical tests. However, there is still no concrete evidence about the association between hip muscle weakness and low back pain and whether this weakness can be assessed with clinical tests. Objective: To assess if there is weakness of the abductor, adductor, extensor, internal and external rotator muscles of the hip in patients with chronic non-specific low back pain, and to verify if there is an association between the Trendelenburg and Step Down tests positivity with the strength of these muscles. Methods: In this cross-sectional case control study, 40 patients with chronic non-specific low back pain and 40 healthy participants were included. The variables assessed were disability using the Roland Morris Disability Questionnaire, pain intensity using the Pain Numerical Rating Scale, muscle strength using a manual isometric dynamometry and the Trendelenburg and Step Down tests. Muscle strength was compared between the two groups using the t test for the independent samples. Subsequently, the association between the clinical tests and the muscular strength was performed through a binary logistic regression analysis. Results: The strength of the abductor (mean difference [MD]: 28.1%, 95% confidence interval [95% CI]: 9.4 to 46.9), adductor (MD: 18.7%, 95% CI: 6.2 to 31.2), external rotator (MD: 7.6%, 95% CI: 0.4 to 14.7), internal rotator (MD 8.7%, 95% CI: 1.5 to 15.8) and extensor muscles of the right hip (MD: 21.1%, 95% CI: 6.2 to 31.2), and of the abductor (MD: 30.4%, 95% CI: 11.9 to 49), adductor (MD 18.4%, 95% CI: 3.7 to 33.2), internal rotator (MD 8.9%, 95% CI: 1 to16.8), and extensor muscles of the left hip (MD 21.6%, 95% CI: 6.6 to 36.5) was significantly statistically lower in patients with chronic non-specific low back pain compared to healthy participants. No statistically significant difference in the positivity of the Trendelenburg and Step Down tests between the groups was found, as well as no association between the tests and the hip muscle strength (p<0.05). Conclusion: Patients with chronic non-specific low back pain present more weakness of the abductor, adductor, and hip extensors muscles than participants without pain. However, there is no difference between participants with and without chronic low back pain in response to the Trendelenburg and Step Down tests, and no association between the tests and the strength assessment. Therefore, Trendelenburg and Step Down tests should not be used in order to assess hip muscle strength in patients with low back pain.